Pengaruh Pendidikan Dan Pelatihan Terhadap Kinerja Pegawai Di Komisi Pemilihan Umum Kabupaten Bombana - Lusi Khairunnisa; Fitri Kumalasari; Niar Astaginy (Profit: Jurnal Manajemen, Bisnis dan Akuntansi, 2023)
This study aims to determine: (1) the effect of education on employee performance in Bombana Regency General Election Commission employees. (2) the effect of training on employee performance in Bombana District Election Commission employees. This research uses a quantitative approach. Collecting data in this study using observation, documentation, and questionnaires. The population of this research is the employees of the General Election Commission of Bombana Regency. While the sample of this study amounted to 33 people. Testing research instruments using validity and reliability tests with SPSS 25.0. The data analysis technique used in this study is the measurement model test (outer model) and the structural model test (inner model) with Smart PLS 3.0. Based on the results of the study it is known that there is a positive and significant influence between the Education variable on Employee Performance in Bombana District Election Commission employees which is shown by a t-statistic value of 0.442 with a P-Value of 0.659. While the variable Training on Employee Performance for the General Election Commission employees of Bombana Regency has a positive and significant effect as shown by the t-statistic value of 3.369 with a P-Value of 0.001.